(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s ((3CMeO Hf GdHUjQ s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOkG jHdZ QVGg hjeJQi GdeRjO efg , hjSJhLH Hg s
(3BNQgG (B:s
(3GdWGLf dZI ai GdWjLf , hcdGgeG ehdO dELJeGY GdWGA hGdLje ai cdeI hGMOI , hPdc dGjchf ai cdGege GdCUdiBNQ GdLRA GdChd hGdMeO ddg s
(3HChdgG Jedjc bOjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs